Politics of Cemetery: Religious Minority in Local Indonesia - Ekaputri, Adethia Septiyani; Sugiarto, Bowo (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
In post-authoritarian Indonesia, although the position of followers of belief (kepercayaan) before the state has relatively positive progress, some still face problems related to their religious identity. One of the followers of belief groups that still receive religious discrimination is the Sapta Darma community in Brebes, Central Java, Indonesia. For example, the followers of Sapta Darma in this region face problems of the availability of cemetery for their deceased members, while just like some other religions; a burial ground is an important part of their religious ritual and identity. This article attempts to explain what restrictions prevent the Sapta Darma community from obtaining cemetery land for their members and what the Sapta Darma community has conducted to settle the problem. This article is based on qualitative research that was conducted in Brebes. This article shows that the availability of Public Cemetery (TPU) and some people’s acceptance of this community serve as the main restriction for the Sapta Darma community to fulfill their need for cemetery land. To settle this problem, they have made some attempts, including seeking the state’s recognition and solution independently.